FILSAFAT ILMU : LANDASAN ONTOLOGI, EPISTEMOLOGI, AKSIOLOGI DALAM KONSELING ISLAM - Ana Bella Puandina; Ja’far Assagaf (Pusat Riset dan Inovasi Nasional, 2023)
This article will examine Islamic counseling associated with the study of philosophy, from the aspects of ontology, epistemology, then axiology. Philosophical values ​​can feed direction and permananan about Islamic counseling. The research method used is literature review or literature study. Integrativity in the main science of Islamic counseling, namely, psychology, communication and Islam. Furthermore, from an epistemology perspective, it is concerned with the implementation and professionalization of the counselor. Then from the aspect of axiology in Islamic counseling which aims to provide assistance provided by counselors to clients in order to find ethical and aesthetic values ​​for the existence of essential (pure) happiness, namely happiness that comes from Allah SWT, the Almighty.